The Influence Of Destination Image And Tourist Attraction On Visitor Satisfaction Bogor Botanical Garden - Manurung, Tarida Marlin Surya; Elizabeth, Maria; Rainanto, Bambang Hengky; Pujiastuti, Sri (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to determine: (1) the influence of Destination Image on the Satisfaction of Visitors to the Bogor Botanical Gardens, (2) the influence of Tourist Attractions on the Satisfaction of Visitors to the Bogor Botanical Gardens, (3) the influence of Destination Image and Tourist Attractions on the Satisfaction of Visitors to the Bogor Botanical Gardens. Data collection was carried out using a questionnaire-based survey distributed to 105 respondents. The sampling technique uses purposive sampling with the characteristics of respondents, namely tourists who have visited the Bogor Botanical Garden once in the past year. The data analysis methods used are descriptive analysis, SEM-PLS analysis, outer model, inner model, and hypothesis testing using SmartPLS version 4 software. Based on the test results, the data obtained are as follows: (1) Destination image partially has a positive and significant effect on visitor satisfaction at the Bogor Botanical Gardens, (2) Tourist attraction partially has a positive and significant effect on visitor satisfaction at the Bogor Botanical Gardens, (3) Destination image and tourist attraction simultaneously have a significant effect on visitor satisfaction at the Bogor Botanical Gardens, (4) Tourist Attraction is the variable that has the most influence on visitor satisfaction to the Bogor Botanical Gardens. Keywords: Tourism, Destination Image, Tourist Attraction, Visitor Satisfaction